Anti-oxidation conductive silver paste for automotive glass and its application

By using specific glass powder and silver powder in automotive glass conductive silver paste and forming a stable glass-silver-glass layer structure through sintering, the problem of oxidation and blackening of traditional conductive silver paste is solved, and efficient anti-oxidation and acid corrosion resistance is achieved.

CN115206583BActive Publication Date: 2025-03-25XIAMEN HAPSTAR ELECTRONIC TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211035132.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-26
Publication Date
2025-03-25
Estimated Expiration
2042-08-26

AI Technical Summary

Technical Problem

Conductive silver paste for traditional automotive glass is prone to oxidation and blackening after several months of use, affecting long-term use performance and aesthetics.

Method used

An antioxidant conductive silver paste for automotive glass is provided, including a first glass powder with a softening point of 545°C, a second glass powder with a softening point of 630 to 650°C, a microsphere silver powder with a 575 to 620°C and a sheet-shaped silver powder with a stable glass-silver layer-glass layer structure through the sintering process.

Benefits of technology

It realizes the stable antioxidant and acid corrosion resistance of the thick film of the conductive line of the automotive glass, avoids the problem of oxidation and blackening, and improves the aesthetics and performance of long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115206583B_ABST
    Figure CN115206583B_ABST
Patent Text Reader

Abstract

The present invention provides an anti-oxidation conductive silver paste for automobile glass, which comprises the following raw materials in mass percentage: 3-9% of a first glass powder, 3-5% of a second glass powder, 50-70% of micro-spherical silver powder, 25-35% of flaky silver powder, 14-21% of an aqueous blending oil, 0.5-2% of a dispersant, 0.5-2% of a defoamer, and 0-1% of a leveling agent; the softening point of the first glass powder is 545° C.; the softening point of the second glass powder is 630-650° C.; the softening points of the micro-spherical silver powder and the flaky silver powder are both 575-620° C. Compared with the prior art, the anti-oxidation conductive silver paste for automobile glass solves the defect that the conventional conductive silver paste for automobile glass turns black after oxidation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electronic pastes for printed circuit technology, and in particular to an anti-oxidation conductive silver paste for automobile glass and application thereof. Background Art

[0002] Compared with other traditional circuit devices, conductive silver paste has the characteristics of high efficiency, good environmental protection, energy saving and emission reduction, and low cost, and is widely used in the preparation of solar cells, sensitive components, resistor networks, aerospace, displays, automotive glass, etc.

[0003] With the development of printed circuit technology, conductive silver paste for automotive glass has become widely used. However, automotive glass printed with conductive silver paste will generally oxidize and turn black after 3 to 6 months of use. This not only affects its long-term performance, but also damages the appearance of the surface.

[0004] In view of this, it is necessary to provide an anti-oxidation conductive silver paste for automotive glass to solve or at least alleviate the technical defect that the above-mentioned conventional conductive silver paste for automotive glass will oxidize and turn black after several months of use. Summary of the invention

[0005] The main purpose of the present invention is to provide an anti-oxidation conductive silver paste for automobile glass, aiming to solve the problem that the conductive silver paste for automobile glass in the prior art will oxidize and turn black after being used for several months.

[0006] To achieve the above object, the present invention provides an antioxidant conductive silver paste for automobile glass, wherein the antioxidant conductive silver paste for automobile glass comprises the following raw materials in percentage by mass: 3-9% of a first glass powder, 3-5% of a second glass powder, 50-70% of microspherical silver powder, 25-35% of flaky silver powder, 14-21% of aqueous blending oil, 0.5-2% of a dispersant, 0.5-2% of a defoaming agent, and 0-1% of a leveling agent.

[0007] The softening point of the first glass powder is 545°C; the softening point of the second glass powder is 630-650°C; the softening points of the microspherical silver powder and the flaky silver powder are both 575-620°C.

[0008] Furthermore, the preparation method of the first glass powder includes:

[0009] S11, by mass percentage, 8-30% silicon dioxide, 3-5% titanium dioxide, 3-6% a first mixture, 42-75% bismuth oxide, 6-15% boric acid and 3-9% a second mixture are added to obtain a first mixed powder; wherein the first mixture includes zinc oxide and aluminum oxide, and the second mixture includes lithium carbonate and potassium carbonate.

[0010] S12, melting the first mixed powder at 1300° C. for 2 hours, and cooling the melted first liquid material by water quenching to form a first glass slag.

[0011] S13, grinding the first glass slag to a particle size D90≤5 μm, and filtering out coarse particles with 800 mesh; and crushing after drying to obtain the first glass powder.

[0012] Furthermore, the melting point of the first glass powder is 545-570°C, and the thermal linear expansion coefficient is 7.6-8.0*10 -6 / ℃, D90 is 4μm, acid resistance test strength is 0.1NH2SO4@80℃, and there is no corrosion or discoloration after continuous immersion for 120h.

[0013] Furthermore, the preparation method of the second glass powder includes:

[0014] S21, by mass percentage, 20-45% silicon dioxide, 0-30% niobium pentoxide, 0.2-5% ferric oxide, 2-15% sodium oxide, 4-25% boron oxide, 1.8-36% zinc oxide, 0-60% bismuth oxide, 0-10% titanium oxide, 0.5-2.5% manganese trioxide, 0-7.5% zirconium oxide, 0-10% yttrium oxide, 0-6% aluminum oxide, 0-5.5% lithium oxide, 0-2.5% potassium oxide and 0-5% fluorine element are mixed to obtain a second mixed powder.

[0015] S22, melting the second mixed powder at 1150° C. for 2 hours, and cooling the melted second liquid material by water quenching to form a second glassy slag.

[0016] S23, grinding the second glass slag and screening out a portion with a particle size of 8 to 10 μm to obtain the second glass powder.

[0017] Furthermore, the particle size of the microspherical silver powder is 0.1-0.2 μm, and the specific surface area is 0.5-1 m 2 / g, bulk density is 1.2~2.4g / mL, tap density is 2~6g / mL, moisture content is ≤0.05%, and loss on burn is ≤0.2%.

[0018] The specific surface area of ​​the flaky silver powder is 2 to 3 m 2 / g, bulk density is 2.5-3.9g / mL, tap density is 1-2g / mL, moisture content is ≤0.1%, and loss on burn is ≤0.15%.

[0019] Furthermore, the aqueous formulated oil comprises the following raw materials in mass percentage: 20-50% of diethylene glycol butyl ether, 15-25% of dipropylene glycol methyl ether, 24-48% of diethylene glycol butyl ether acetate, 4-8% of ethyl cellulose, and 5-10% of aqueous modified acrylic resin.

[0020] Furthermore, the dispersant is one or more of SILCOWETD-504 / PEG, BYK-312, and L-18.

[0021] The defoaming agent is one or more of TSA-750S and SILCO AF 100.

[0022] The leveling agent is Glide Rad 2600, DC57 or SILCO FLW B-127.

[0023] The present invention also provides a method for preparing an anti-oxidation conductive silver paste for automobile glass, comprising:

[0024] S31, mixing the first glass powder, the second glass powder, the microspherical silver powder, the flake silver powder, the water-based mixing oil, the dispersant, the defoaming agent and the leveling agent according to the aforementioned composition ratio to obtain a mixed slurry.

[0025] S32, sequentially subjecting the mixed slurry to coarse grinding, fine grinding and fine grinding; filtering the product after the fine grinding and removing large particles of impurities; and then degassing and grinding the product after the degassing to obtain the antioxidant conductive silver paste for automotive glass.

[0026] The present invention also provides an application of an antioxidant conductive silver paste for automotive glass. The antioxidant conductive silver paste for automotive glass prepared by the above preparation method is screen-printed to obtain a silver paste thick film, and the surface is dried at 150-180° C. for 5 minutes. The dried silver paste thick film is sintered at 550-730° C. to obtain an antioxidant conductive circuit thick film for automotive glass.

[0027] Furthermore, the sintering process includes: heating the dried silver paste thick film to 550-730° C. at a heating rate of 5° C. / min, keeping the temperature for 10 minutes, and cooling to room temperature to obtain the anti-oxidation conductive circuit thick film for automotive glass.

[0028] The present invention has the following beneficial effects:

[0029] The raw materials of the anti-oxidation conductive silver paste for automobile glass provided by the present invention include a first glass powder with a softening point of 545°C, a second glass powder with a softening point of 630-650°C, and micro-spherical silver powder and flaky silver powder with a softening point of 575-620°C. The anti-oxidation conductive silver paste for automobile glass is made into a silver paste thick film. During the sintering process of the silver paste thick film, the first glass powder first reaches the softening point and begins to melt, penetrates the micro-spherical silver powder and the flaky silver powder, reaches the surface of the printed float glass, forms a stable anchoring structure, and firmly adheres to the surface of the glass layer; as the temperature rises, when the softening points of the micro-spherical silver powder and the flaky silver powder are reached, the micro-spherical silver powder melts and penetrates into the mesh gaps of the flaky silver powder, and the micro-spherical silver powder overlaps with the flaky silver powder to form a flat and dense silver layer; during the sintering process, when the temperature reaches its softening point, the second glass powder melts and floats to the surface of the aforementioned silver layer; finally, an anti-oxidation conductive circuit thick film for automobile glass is formed with a layer of silver sandwiched between two layers of glass.

[0030] The anti-oxidation conductive circuit thick film for automobile glass has a stable glass layer-silver layer-glass layer structure, and the anti-oxidation ability and acid corrosion resistance of the structure are both excellent. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0032] Figure 1 This is a test diagram of the anti-oxidation ability of the anti-oxidation conductive circuit thick film for automobile glass in Example 1;

[0033] Figure 2 This is a test diagram of the antioxidant capacity of the antioxidant conductive circuit thick film for automobile glass in Example 2;

[0034] Figure 3 This is a graph showing the antioxidant capacity of the antioxidant conductive circuit thick film for automobile glass in Example 3;

[0035] Figure 4 This is a test diagram of the anti-oxidation ability of the conductive circuit thick film for automobile glass in Comparative Example 1;

[0036] Figure 5 This is a test chart of the anti-oxidation ability of thick films of conductive silver paste sold on the market.

[0037] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with the implementation methods and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] It should be noted that the following embodiments and features in the embodiments can be combined with each other without conflict. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments rather than to limit the scope of protection of the present invention.

[0040] Unless otherwise defined, all technical and scientific terms used in the present invention and the technical personnel in the art grasp the prior art and the record of the present invention, and any method, equipment and material of the prior art similar or equivalent to the method, equipment and material in the embodiments of the present invention can also be used to realize the present invention. When the embodiment gives a numerical range, it should be understood that, unless otherwise specified in the present invention, the two endpoints of each numerical range and any numerical value between the two endpoints can be selected. The test method of the following examples without specifying the specific conditions is usually according to conventional conditions, or according to the conditions recommended by each manufacturer. The materials or reagents required in the following examples are all purchased from the market unless otherwise specified.

[0041] In order to solve the use of conductive silver paste for automotive glass in the prior art, the present invention provides an antioxidant conductive silver paste for automotive glass, the antioxidant conductive silver paste for automotive glass comprises the following raw materials in percentage by mass: 3-9% first glass powder, 3-5% second glass powder, 50-70% microspherical silver powder, 25-35% flaky silver powder, 14-21% aqueous formulation oil, 0.5-2% dispersant, 0.5-2% defoaming agent, and 0-1% leveling agent.

[0042] The softening point of the first glass powder is 545°C; the softening point of the second glass powder is 630-650°C; the softening points of the microspherical silver powder and the flaky silver powder are both 575-620°C.

[0043] When the anti-oxidation conductive silver paste for automobile glass is made into a silver paste thick film, during the sintering process of the silver paste thick film, the first glass powder first reaches the softening point and begins to melt, penetrates the micro-spherical silver powder and the flaky silver powder, reaches the surface of the printed float glass, forms a stable anchoring structure, and firmly adheres to the surface of the glass layer; as the temperature rises, when the softening points of the micro-spherical silver powder and the flaky silver powder are reached, the micro-spherical silver powder melts and penetrates into the mesh gaps of the flaky silver powder, and the micro-spherical silver powder overlaps with the flaky silver powder to form a flat and dense silver layer; during the sintering process, when the temperature reaches its softening point, the second glass powder melts and floats to the surface of the aforementioned silver layer; finally, an anti-oxidation conductive circuit thick film for automobile glass with a layer of silver sandwiched between two glass layers is formed.

[0044] Furthermore, the preparation method of the first glass powder includes:

[0045] S11, by mass percentage, 8-30% silicon dioxide, 3-5% titanium dioxide, 3-6% a first mixture, 42-75% bismuth oxide, 6-15% boric acid and 3-9% a second mixture are added to obtain a first mixed powder; wherein the first mixture includes zinc oxide and aluminum oxide, and the second mixture includes lithium carbonate and potassium carbonate.

[0046] 6-15% by mass of boric acid can reduce the softening point of the first glass powder and have a stable thermal expansion coefficient. The first mixture used is composed of zinc oxide and aluminum oxide, and the zinc and aluminum ions are cloud-deformed to form a more compact glass phase structure.

[0047] S12, melting the first mixed powder at 1300° C. for 2 hours, and cooling the molten first liquid material by water quenching to form a first glassy slag.

[0048] S13, grinding the first glass slag to a particle size D90≤5 μm, and filtering out coarse particles with 800 mesh; and crushing after drying to obtain a first glass powder.

[0049] Furthermore, the melting point of the first glass powder is 545-570°C, and the thermal linear expansion coefficient is 7.6-8.0*10 -6 / ℃, D90 is 4μm, acid resistance test strength is 0.1NH2SO4@80℃, and there is no corrosion or discoloration after continuous immersion for 120h.

[0050] Due to the special selection of titanium dioxide seeds and the unique ratio as above, combined with the spraying process of glass powder making by oxygen-acetylene spraying equipment, stable Ti-Si crystals can be formed in the high temperature section of sintering, floating on the surface of the silver layer structure, and at the same time having a stable glass structure, which can achieve super acid corrosion resistance detected by 0.1NH2SO4 80℃.

[0051] Furthermore, the preparation method of the second glass powder includes:

[0052] S21, by mass percentage, 20-45% silicon dioxide, 0-30% niobium pentoxide, 0.2-5% ferric oxide, 2-15% sodium oxide, 4-25% boron oxide, 1.8-36% zinc oxide, 0-60% bismuth oxide, 0-10% titanium oxide, 0.5-2.5% manganese trioxide, 0-7.5% zirconium oxide, 0-10% yttrium oxide, 0-6% aluminum oxide, 0-5.5% lithium oxide, 0-2.5% potassium oxide and 0-5% fluorine element are mixed to obtain a second mixed powder.

[0053] This ratio does not contain any harmful ingredients and will not produce any toxic effects during the sintering process.

[0054] S22, melting the second mixed powder at 1150° C. for 2 hours, and cooling the molten second material liquid by water quenching to form a second glassy slag.

[0055] S23, grinding the second glass slag and screening out a portion with a particle size of 8 to 10 μm to obtain a second glass powder.

[0056] Furthermore, the particle size of the microspherical silver powder is 0.1 to 0.2 μm, and the specific surface area is 0.5 to 1 m 2 / g, bulk density is 1.2~2.4g / mL, tap density is 2~6g / mL, moisture content is ≤0.05%, and loss on burn is ≤0.2%.

[0057] The specific surface area of ​​flaky silver powder is 2 to 3 m 2 / g, bulk density is 2.5-3.9g / mL, tap density is 1-2g / mL, moisture content is ≤0.1%, and loss on burn is ≤0.15%.

[0058] Furthermore, the aqueous formulation oil comprises the following raw materials in percentage by weight: 20-50% of diethylene glycol butyl ether, 15-25% of dipropylene glycol methyl ether, 24-48% of diethylene glycol butyl ether acetate, 4-8% of ethyl cellulose, and 5-10% of aqueous modified acrylic resin.

[0059] Furthermore, the dispersant is one or more of SILCOWETD-504 / PEG, BYK-312, and L-18.

[0060] Specifically, the dispersant may be Japanese Kao L-18.

[0061] The defoaming agent is one or more of TSA-750S and SILCO AF 100.

[0062] Specifically, the defoaming agent can be American Momentive TSA-750S.

[0063] The leveling agent is Glide Rad 2600, DC57 or SILCO FLW B-127.

[0064] Specifically, the leveling agent may be Dow Corning DC57.

[0065] The present invention also provides a method for preparing an anti-oxidation conductive silver paste for automobile glass, comprising:

[0066] S31, mixing the first glass powder, the second glass powder, the microspherical silver powder, the flake silver powder, the water-based mixing oil, the dispersant, the defoaming agent and the leveling agent according to the aforementioned composition ratio to obtain a mixed slurry.

[0067] S32, sequentially subjecting the mixed slurry to coarse grinding, fine grinding and fine grinding; filtering the product after the fine grinding and removing large particle impurities; and then degassing and grinding the product after the degassing to obtain an antioxidant conductive silver paste for automotive glass.

[0068] The present invention also provides an application of an antioxidant conductive silver paste for automotive glass. The antioxidant conductive silver paste for automotive glass prepared by the above preparation method is screen printed (printed on a printing glass plate) to obtain a silver paste thick film, and the surface is dried at 150-180° C. for 5 minutes. The dried silver paste thick film is sintered at 550-730° C. to obtain an antioxidant conductive circuit thick film for automotive glass.

[0069] Furthermore, the sintering process includes: heating the dried silver paste thick film to 550-730°C at a heating rate of 5°C / min, keeping the temperature for 10 minutes, and cooling to room temperature to obtain an anti-oxidation conductive circuit thick film for automotive glass.

[0070] For further understanding of the present invention, examples are given below:

[0071] Example 1

[0072] 1. Preparation of the first glass powder

[0073] By mass percentage, 8% silicon dioxide, 4% titanium dioxide, 6% a mixture of zinc oxide and aluminum oxide, 65% bismuth oxide, 10% boric acid and 7% a mixture of lithium carbonate and potassium carbonate are uniformly mixed to obtain a first mixed powder.

[0074] Set the pre-cleaned alumina kiln to 800°C, heat it up and fire it for 30 minutes, then raise the kiln temperature to 1300°C, fill the configured first mixed powder into the oxygen-acetylene spraying device, spray it into the heated alumina kiln, keep it warm for 2 hours, release the evenly molten first liquid into cold water, and quench it with water to form a first glassy slag.

[0075] The first glass slag: anhydrous ethanol: zirconium oxide balls are mixed in a ratio of 1:1:1, ground using a grinder to a particle size of D90 ≤ 5 μm, then filtered out with 800 mesh to remove coarse particles, the filtered particles are placed in a plate and dried in an oven at 60°C, and then crushed again into a powder with uniform particles by high-pressure airflow. The particle size D90 ≤ 5 μm is detected, and the first glass powder with a softening point of 545°C is obtained.

[0076] 2. Prepare the second glass powder with a softening point of 630°C

[0077] By mass percentage, 20% silicon dioxide, 10% niobium pentoxide, 0.5% ferric oxide, 12% sodium oxide, 18% boron oxide, 6.5% zinc oxide, 2% bismuth oxide, 8% titanium oxide, 1.5% manganese trioxide, 3.5% zirconium oxide, 6% yttrium oxide, 3% aluminum oxide, 2.5% lithium oxide, 1.5% potassium oxide and 5% fluorine element are uniformly mixed to obtain a second mixed powder.

[0078] Set the pre-cleaned alumina kiln to 700°C, heat it up and fire it for 30 minutes, then raise the kiln temperature to 1150°C, load the prepared second mixed powder into the oxygen-acetylene spraying device, spray it into the heated alumina kiln, keep it warm for 2 hours, release the uniformly molten second liquid into cold water, cool it rapidly, and obtain a second glassy slag.

[0079] The second glass slag is ball-milled, and a portion with a particle size of 8 to 10 μm is obtained by screening to obtain a second glass powder.

[0080] 3. Preparation of anti-oxidation conductive silver paste for automotive glass

[0081] 4% of the first glass powder, 3% of the second glass powder, 50% of the microspherical silver powder, 25% of the flaky silver powder, 15% of the aqueous blending oil, 1.5% of the dispersant, 0.5% of the defoaming agent and 1% of the leveling agent were weighed by mass and put into a stainless steel batching barrel, and dispersed evenly by a high-speed disperser. The speed of the high-speed disperser was set to 900 r / min, and the stirring time was 5 h to obtain a mixed slurry.

[0082] The mixed slurry is put into a hydraulic three-roll mill for grinding, and after six times of coarse grinding, eight times of fine grinding, and five times of fine grinding, vacuum filtration is performed to remove large particles of impurities, and degassing treatment is performed. Finally, it is ground and dispersed twice again and canned to obtain an antioxidant conductive silver paste for automotive glass.

[0083] 4. Sintering into anti-oxidation thick film for automotive glass and testing the anti-oxidation ability

[0084] (1) The anti-oxidation conductive silver paste for automobile glass obtained in step 3 is screen-printed onto a printing glass plate using a screen printer, and the surface is dried at 150-180° C. / 5 minutes.

[0085] The dried product was placed in a box-type resistance furnace, the heating rate of the box-type resistance furnace was adjusted to 5°C / min, the temperature was raised to 650°C for sintering, and after keeping the temperature for 10 minutes, the box-type resistance furnace body was cooled to room temperature to obtain a dense anti-oxidation conductive circuit thick film for automotive glass.

[0086] (2) Antioxidant capacity test

[0087] Add 1g of sulfur to 200g of anhydrous ethanol to prepare a soaking solution; place the obtained antioxidant conductive circuit thick film for automotive glass in the soaking solution; take it out after 24 hours and observe the color change, such as Figure 1 In order to comply with the relevant provisions of the Patent Examination Guidelines on drawings in the specification, Figure 1 Adjust to an uncolored grayscale image; all subsequent figures are processed in this way and will not be described in detail.

[0088] Example 2

[0089] 1. Preparation of the first glass powder

[0090] By mass percentage, 10% silicon dioxide, 3% titanium dioxide, 5% a mixture of zinc oxide and aluminum oxide, 70% bismuth oxide, 8% boric acid and 4% a mixture of lithium carbonate and potassium carbonate are uniformly mixed to obtain a first mixed powder.

[0091] Set the pre-cleaned alumina kiln to 800°C, heat it up and fire it for 30 minutes, then raise the kiln temperature to 1300°C, fill the configured first mixed powder into the oxygen-acetylene spraying device, spray it into the heated alumina kiln, keep it warm for 2 hours, release the evenly molten first liquid into cold water, and quench it with water to form a first glassy slag.

[0092] The first glass slag: anhydrous ethanol: zirconium oxide balls are mixed in a ratio of 1:1:1, ground using a grinder to a particle size of D90 ≤ 5 μm, then filtered out with 800 mesh to remove coarse particles, the filtered particles are placed in a plate and dried in an oven at 60°C, and then crushed again into a powder with uniform particles by high-pressure airflow. The particle size D90 ≤ 5 μm is detected, and the first glass powder with a softening point of 545°C is obtained.

[0093] 2. Prepare the second glass powder with a softening point of 640°C

[0094] Calculated by mass percentage, 23% silicon dioxide, 8% niobium pentoxide, 0.5% ferric oxide, 11% sodium oxide, 16% boron oxide, 7.5% zinc oxide, 2% bismuth oxide, 9% titanium oxide, 1.5% manganese trioxide, 3.5% zirconium oxide, 5% yttrium oxide, 3% aluminum oxide, 3.5% lithium oxide, 1.5% potassium oxide and 5% fluorine element are uniformly mixed to obtain a second mixed powder.

[0095] Set the pre-cleaned alumina kiln to 700°C, heat it up and fire it for 30 minutes, then raise the kiln temperature to 1150°C, load the prepared second mixed powder into the oxygen-acetylene spraying device, spray it into the heated alumina kiln, keep it warm for 2 hours, release the uniformly molten second liquid into cold water, cool it rapidly, and obtain a second glassy slag.

[0096] The second glass slag is ball-milled, and a portion with a particle size of 8 to 10 μm is obtained by screening to obtain a second glass powder.

[0097] 3. Preparation of anti-oxidation conductive silver paste for automotive glass

[0098] 4% of the first glass powder, 3% of the second glass powder, 51% of the microspherical silver powder, 25% of the flaky silver powder, 14% of the aqueous blending oil, 1.5% of the dispersant, 0.5% of the defoaming agent and 1% of the leveling agent were weighed by mass and put into a stainless steel batching barrel, and dispersed evenly by a high-speed disperser. The speed of the high-speed disperser was set to 900 r / min, and the stirring time was 5 h to obtain a mixed slurry.

[0099] The mixed slurry is put into a hydraulic three-roll mill for grinding, and after six times of coarse grinding, eight times of fine grinding, and five times of fine grinding, vacuum filtration is performed to remove large particles of impurities, and degassing treatment is performed. Finally, it is ground and dispersed twice again and canned to obtain an antioxidant conductive silver paste for automotive glass.

[0100] 4. Sintering into anti-oxidation thick film for automotive glass and testing the anti-oxidation ability

[0101] (1) The anti-oxidation conductive silver paste for automobile glass obtained in step 3 is screen-printed onto a printing glass plate using a screen printer, and the surface is dried at 150-180° C. / 5 minutes.

[0102] The dried product was placed in a box-type resistance furnace, the heating rate of the box-type resistance furnace was adjusted to 5°C / min, the temperature was raised to 650°C for sintering, and after keeping the temperature for 10 minutes, the box-type resistance furnace body was cooled to room temperature to obtain a dense anti-oxidation conductive circuit thick film for automotive glass.

[0103] (2) Antioxidant capacity test

[0104] Add 1g of sulfur to 200g of anhydrous ethanol to prepare a soaking solution; place the obtained antioxidant conductive circuit thick film for automotive glass in the soaking solution; take it out after 24 hours and observe the color change, such as Figure 2 shown.

[0105] Example 3

[0106] 1. Preparation of the first glass powder

[0107] By mass percentage, 11% silicon dioxide, 3% titanium dioxide, 4% a mixture of zinc oxide and aluminum oxide, 72% bismuth oxide, 7% boric acid and 3% a mixture of lithium carbonate and potassium carbonate are uniformly mixed to obtain a first mixed powder.

[0108] Set the pre-cleaned alumina kiln to 800°C, heat it up and fire it for 30 minutes, then raise the kiln temperature to 1300°C, fill the configured first mixed powder into the oxygen-acetylene spraying device, spray it into the heated alumina kiln, keep it warm for 2 hours, release the evenly molten first liquid into cold water, and quench it with water to form a first glassy slag.

[0109] The first glass slag: anhydrous ethanol: zirconium oxide balls are mixed in a ratio of 1:1:1, ground using a grinder to a particle size of D90 ≤ 5 μm, then filtered out with 800 mesh to remove coarse particles, the filtered particles are placed in a plate and dried in an oven at 60°C, and then crushed again into a powder with uniform particles by high-pressure airflow. The particle size D90 ≤ 5 μm is detected, and the first glass powder with a softening point of 545°C is obtained.

[0110] 2. Prepare the second glass powder with a softening point of 650°C

[0111] By mass percentage, 28% silicon dioxide, 6% niobium pentoxide, 0.5% ferric oxide, 8% sodium oxide, 13% boron oxide, 9.5% zinc oxide, 3% bismuth oxide, 9% titanium oxide, 1.5% manganese trioxide, 3.5% zirconium oxide, 4% yttrium oxide, 3% aluminum oxide, 3.5% lithium oxide, 2.5% potassium oxide and 5% fluorine element are uniformly mixed to obtain a second mixed powder.

[0112] Set the pre-cleaned alumina kiln to 700°C, heat it up and fire it for 30 minutes, then raise the kiln temperature to 1150°C, load the prepared second mixed powder into the oxygen-acetylene spraying device, spray it into the heated alumina kiln, keep it warm for 2 hours, release the uniformly molten second liquid into cold water, cool it rapidly, and obtain a second glassy slag.

[0113] The second glass slag is ball-milled, and a portion with a particle size of 8 to 10 μm is obtained by screening to obtain a second glass powder.

[0114] 3. Preparation of anti-oxidation conductive silver paste for automotive glass

[0115] 3% of the first glass powder, 3% of the second glass powder, 53% of the microspherical silver powder, 25% of the flaky silver powder, 14% of the aqueous blending oil, 0.5% of the dispersant, 0.5% of the defoaming agent and 1% of the leveling agent were weighed by mass and put into a stainless steel batching barrel, and dispersed evenly by stirring with a high-speed disperser, wherein the speed of the high-speed disperser was set to 900 r / min, and the stirring time was 5 h to obtain a mixed slurry.

[0116] The mixed slurry is put into a hydraulic three-roll mill for grinding, and after six times of coarse grinding, eight times of fine grinding, and five times of fine grinding, vacuum filtration is performed to remove large particles of impurities, and degassing treatment is performed. Finally, it is ground and dispersed twice again and canned to obtain an antioxidant conductive silver paste for automotive glass.

[0117] 4. Sintering into anti-oxidation thick film for automotive glass and testing the anti-oxidation ability

[0118] (1) The anti-oxidation conductive silver paste for automobile glass obtained in step 3 is screen-printed onto a printing glass plate using a screen printer, and the surface is dried at 150-180° C. / 5 minutes.

[0119] The dried product was placed in a box-type resistance furnace, the heating rate of the box-type resistance furnace was adjusted to 5°C / min, the temperature was raised to 650°C for sintering, and after keeping the temperature for 10 minutes, the box-type resistance furnace body was cooled to room temperature to obtain a dense anti-oxidation conductive circuit thick film for automotive glass.

[0120] (2) Antioxidant capacity test

[0121] 1 g of elemental sulfur was added to 200 g of anhydrous ethanol to prepare a soaking solution; the obtained antioxidant conductive circuit thick film for automotive glass was placed in the soaking solution; it was taken out after 24 hours and the color change was observed, as shown in Example 3.

[0122] Comparative Example 1

[0123] Different from Example 1, the second glass powder is not added during the preparation of the conductive silver paste.

[0124] 1. Preparation of conductive silver paste

[0125] 7% of the first glass powder, 50% of the microspherical silver powder, 25% of the flaky silver powder, 15% of the aqueous blending oil, 1.5% of the dispersant, 0.5% of the defoaming agent and 1% of the leveling agent were weighed by mass percentage, put into a stainless steel batching barrel, and dispersed evenly by a high-speed disperser. The speed of the high-speed disperser was set to 900 r / min, and the stirring time was 5 h to obtain a mixed slurry.

[0126] The mixed slurry is put into a hydraulic three-roll mill for grinding, and after six times of coarse grinding, eight times of fine grinding, and five times of fine grinding, vacuum filtration is performed to remove large particles of impurities, and degassing treatment is performed. Finally, it is ground and dispersed twice again and canned to obtain the conductive silver paste for automotive glass.

[0127] 2. Sintering into thick film for automotive glass and testing its antioxidant capacity

[0128] (1) The conductive silver paste for automobile glass obtained in step 1 is screen-printed onto a printing glass plate using a screen printer, and the surface is dried at 150-180° C. / 5 minutes.

[0129] The dried product was placed in a box-type resistance furnace, the heating rate of the box-type resistance furnace was adjusted to 5°C / min, the temperature was raised to 650°C for sintering, and after keeping the temperature for 10 minutes, the box-type resistance furnace body was cooled to room temperature to obtain a dense conductive circuit thick film for automotive glass.

[0130] (2) Antioxidant capacity test

[0131] Add 1g of sulfur to 200g of anhydrous ethanol to prepare a soaking solution; place the obtained automotive glass conductive circuit thick film in the soaking solution; take it out after 6 hours and observe the color change, such as Figure 4 shown.

[0132] Analysis example 1

[0133] Analysis of Antioxidation Ability of Conductive Silver Paste

[0134] Among them, the conductive silver paste sold on the market takes the 778 model conductive silver paste sold by Shanghai Baoyin Electronic Materials Co., Ltd. as an example, and adopts the same sintering method as in Example 1 to sinter to obtain a thick film of the conductive silver paste sold on the market, and conducts an antioxidant capacity test. The specific test process is as follows:

[0135] Add 1g of sulfur to 200g of anhydrous ethanol to prepare an immersion solution; place the thick film of the commercially available conductive silver paste in the immersion solution; take it out after 4 hours and observe the color change, such as Figure 5 shown.

[0136] The antioxidant capacity of Example 1, Example 2, Example 3, Comparative Example and commercially available conductive silver paste is shown in Table 1.

[0137] Table 1 Antioxidant capacity test analysis

[0138]

[0139] It can be seen that the anti-oxidation conductive silver paste for automobile glass solves the defect of the traditional conductive silver paste for automobile glass being oxidized and blackened after use. The anti-oxidation conductive circuit thick film for automobile glass sintered in the present invention has excellent anti-oxidation ability and acid corrosion resistance, conforms to green chemistry, and has strong applicability.

[0140] In summary, the above technical solutions of the present invention are only preferred embodiments of the present invention, and the patent scope of the present invention is not limited thereto. All equivalent structural changes made by using the contents of the present invention specification and drawings under the technical concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. An anti-oxidation conductive silver paste for automotive glass, characterized in that: The anti-oxidation conductive silver paste for automobile glass comprises the following raw materials in percentage by weight: 3-9% of a first glass powder, 3-5% of a second glass powder, 50-70% of micro-spherical silver powder, 25-35% of flaky silver powder, 14-21% of water-based blending oil, 0.5-2% of a dispersant, 0.5-2% of a defoamer, and 0-1% of a leveling agent; The softening point of the first glass powder is 545°C; the softening point of the second glass powder is 630-650°C; the softening points of the microspherical silver powder and the flaky silver powder are both 575-620°C.

2. The anti-oxidation conductive silver paste for automobile glass according to claim 1, characterized in that: The preparation method of the first glass powder comprises: S11, by mass percentage, 8-30% silicon dioxide, 3-5% titanium dioxide, 3-6% of a first mixture, 42-75% bismuth oxide, 6-15% boric acid, and 3-9% of a second mixture to obtain a first mixed powder; wherein the first mixture comprises zinc oxide and aluminum oxide, and the second mixture comprises lithium carbonate and potassium carbonate; S12, melting the first mixed powder at 1300° C. for 2 hours, and cooling the melted first liquid by water quenching to form a first vitreous slag; S13, grinding the first glass slag to a particle size D90≤5 μm, and filtering out coarse particles with 800 mesh; and crushing after drying to obtain the first glass powder.

3. The anti-oxidation conductive silver paste for automobile glass according to claim 2, characterized in that: The melting point of the first glass powder is 545-570°C, and the thermal linear expansion coefficient is 7.6-8.0 10 -6 / ℃, D90 is 4μm, acid resistance test strength is 0.1NH2SO4 @80℃, and there is no corrosion or discoloration after continuous immersion for 120h.

4. The anti-oxidation conductive silver paste for automobile glass according to claim 1, characterized in that: The preparation method of the second glass powder comprises: S21, by mass percentage, 20-45% silicon dioxide, 6-30% niobium pentoxide, 0.2-5% ferric oxide, 2-15% sodium oxide, 4-25% boron oxide, 1.8-36% zinc oxide, 2-60% bismuth oxide, 8-10% titanium oxide, 0.5-2.5% manganese trioxide, 3.5-7.5% zirconium oxide, 4-10% yttrium oxide, 3-6% aluminum oxide, 2.5-5.5% lithium oxide, 1.5-2.5% potassium oxide and 5% fluorine element are mixed to obtain a second mixed powder; S22, melting the second mixed powder at 1150° C. for 2 hours, and cooling the melted second liquid by water quenching to form a second glassy slag; S23, grinding the second glass slag and screening out a portion with a particle size of 8-10 μm to obtain the second glass powder.

5. The anti-oxidation conductive silver paste for automobile glass according to claim 1, characterized in that: The particle size of the microspherical silver powder is 0.1-0.2 μm, and the specific surface area is 0.5-1 m 2 / g, bulk density is 1.2~2.4g / mL, tap density is 2~6g / mL, moisture content is ≤0.05%, and loss on burn is ≤0.2%; The specific surface area of ​​the flaky silver powder is 2 to 3 m 2 / g, bulk density is 2.5~3.9g / mL, tap density is 1~2g / mL, moisture content is ≤0.1%, and loss on burn is ≤0.15%.

6. The anti-oxidation conductive silver paste for automobile glass according to claim 1, characterized in that: The aqueous formulated oil comprises the following raw materials in mass percentage: 20-50% of diethylene glycol butyl ether, 15-25% of dipropylene glycol methyl ether, 24-48% of diethylene glycol butyl ether acetate, 4-8% of ethyl cellulose, and 5-10% of aqueous modified acrylic resin.

7. The anti-oxidation conductive silver paste for automobile glass according to claim 1, characterized in that: The dispersant is one or more of SILCO WET D-504 / PEG, BYK-312, and L-18; The defoaming agent is one or more of TSA-750S and SILCO AF 100; The leveling agent is Glide Rad 2600, DC57 or SILCO FLW B-127.

8. A method for preparing an antioxidant conductive silver paste for automotive glass, characterized in that: include: S31, mixing the first glass powder, the second glass powder, the microspherical silver powder, the flaky silver powder, the aqueous mixing oil, the dispersant, the defoaming agent and the leveling agent according to the composition ratio of the antioxidant conductive silver paste for automotive glass according to claim 1 to obtain a mixed paste; S32, sequentially performing coarse grinding, fine grinding, and fine grinding on the mixed slurry; filtering the product after the fine grinding to remove large particle impurities; The degassing treatment is then performed, and the product after the degassing treatment is ground to obtain the anti-oxidation conductive silver paste for automobile glass.

9. An application of an anti-oxidation conductive silver paste for automotive glass, characterized in that: The anti-oxidation conductive silver paste for automobile glass prepared by the preparation method described in claim 8 is screen-printed to obtain a silver paste thick film, the surface is dried at 150-180° C. for 5 minutes, and the dried silver paste thick film is sintered at 650-730° C. to obtain an anti-oxidation conductive circuit thick film for automobile glass.

10. The use of the antioxidant conductive silver paste for automobile glass according to claim 9, characterized in that: The sintering process includes: heating the dried silver paste thick film to 650-730°C at a heating rate of 5°C / min, keeping the temperature for 10 minutes, and cooling to room temperature to obtain the anti-oxidation conductive circuit thick film for automotive glass.

Citation Information

Patent Citations

  • Sliver electrode slurry for back electric field of silicon solar cell and preparation method thereof

    CN102354545A

  • Low-resistance high-efficiency lead-free back silver pulp for amorphous silicon solar battery

    CN104505139A